PERTIMBANGAN PENETAPAN HUKUMAN BAGI PENGGUNA NARKOTIKA DAN EFEKTIVITAS SERTA HAMBATAN-HAMBATAN YANG DIHADAPI DALAM PROSES PEMBINAAN PENGGUNA NARKOTIKA - Pelle, Essa Felistya Naldy; Manafe, Deddy R. CH; Djara Dima, Adrianus (Petitum Law Journal, 2024)
Narcotics is an abbreviation of narcotics and drugs/dangerous substances which were originally intended for medical purposes or health services. Every year, around 15 thousand people die because of drug use. Based on data from the Directorate General of Corrections, as of September 2016, there were 24,914 narcotics users in prisons. This proves that the number of drug users increases quite rapidly every year. This research is empirical juridical legal research. The types and sources of data for this research are primary data and secondary data. Respondents in this research were court judges, heads of correctional institutions, officers and staff of correctional institutions. The data collection techniques used were field observations and interviews. The technique used in analyzing data is descriptive qualitative.The results of this research show that: (1) In determining punishment for narcotics users, the Kupang District Court has several considerations in imposing sentences, these considerations are: (a) Identification of convicts who use narcotics, (b) Type of narcotics, (c) History narcotics violations, (d) Involvement with drug dealers. (2) There are two Guidance Patterns implemented at the Kupang Correctional Institution in carrying out guidance for prisoners at the Kupang Correctional Institution, namely personality guidance and independence guidance. (3) Obstacles in the process of developing narcotics convicts faced by the Kupang Class II A Penitentiary, namely: (a) Lack of socialization from BNN and social rehabilitation (b) No rehabilitation from BNN (c) No guarantor of parole from prison.